2013
DOI: 10.1093/cid/cit196
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Genetic Background, Traditional Risk Factors, and HIV-Related Factors to Coronary Artery Disease Events in HIV-Positive Persons

Abstract: In the setting of HIV infection, the effect of an unfavorable genetic background was similar to traditional CAD risk factors and certain adverse antiretroviral exposures. Genetic testing may provide prognostic information complementary to family history of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 35 publications
3
41
0
Order By: Relevance
“…Some of the limitations of previous studies included small numbers of HIV-infected patients, a deficiency of rigorously adjudication of CV events, and inconsistent adjustment for confounding factors, such as smoking, that occur at much higher rates in the HIV population. The WG also noted that there was not enough information to fully understand the contributions to HIV-related CAD of traditional risk factors, such as hyperlipidemia, hypertension, and smoking versus the detrimental effects of the HIV virus itself, associated inflammation, ART, and coinfections (32,33). …”
Section: Resultsmentioning
confidence: 99%
“…Some of the limitations of previous studies included small numbers of HIV-infected patients, a deficiency of rigorously adjudication of CV events, and inconsistent adjustment for confounding factors, such as smoking, that occur at much higher rates in the HIV population. The WG also noted that there was not enough information to fully understand the contributions to HIV-related CAD of traditional risk factors, such as hyperlipidemia, hypertension, and smoking versus the detrimental effects of the HIV virus itself, associated inflammation, ART, and coinfections (32,33). …”
Section: Resultsmentioning
confidence: 99%
“…We note that there is no universal value for a in today's genetic tests, and the optimal value of a (for maximum utility) might change based on the type of the test. For example, a recent study on cardiovascular disease shows that a = 4 is sufficient to determine a patient's susceptibility to this disease [30]. Comparing Figs.…”
Section: Obfuscation Methodsmentioning
confidence: 99%
“…As a result of our extensive collaboration with geneticists, clinicians, and biologists, we concluded that a DNA string comparison is insufficient in many medical tests (that use genomic data) [5,27,30] and would not be enough to pave the way to personalized medicine. As it will become clearer in the next sections, for each genetic test, specific variants must be considered individually.…”
Section: Related Workmentioning
confidence: 99%
“…The authors report that the effect of unfavorable genetic background was similar to traditional CAD risk factors and certain adverse antiretroviral exposures. The authors concluded that genetic testing might provide prognostic information complementary to the family history of CAD [64] .…”
Section: Abca1 Hepatic Lipase (Lipc) and Cholesteryl Estermentioning
confidence: 99%